2018
DOI: 10.1038/s41598-018-29852-2
|View full text |Cite
|
Sign up to set email alerts
|

S100P enhances the motility and invasion of human trophoblast cell lines

Abstract: S100P has been shown to be a marker for carcinogenesis where its expression in solid tumours correlates with metastasis and a poor patient prognosis. This protein’s role in any physiological process is, however, unknown. Here we first show that S100P is expressed both in trophoblasts in vivo as well as in some corresponding cell lines in culture. We demonstrate that S100P is predominantly expressed during the early stage of placental formation with its highest expression levels occurring during the first trime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(63 citation statements)
references
References 94 publications
10
53
0
Order By: Relevance
“…The "p" in the name reflects the location of its first isolation, the placenta. Expression of the S100P protein is 90-to 200-fold higher in the placenta than in any other organ [22,23,20]. As might be expected, it is predominantly expressed in the early stages of gestation during placental formation, and this high level of expression continues through the first trimester of pregnancy/ It is reduced by 50% during the second and third trimesters of gestation [22,24].…”
Section: General Information About S100p Proteinmentioning
confidence: 63%
See 2 more Smart Citations
“…The "p" in the name reflects the location of its first isolation, the placenta. Expression of the S100P protein is 90-to 200-fold higher in the placenta than in any other organ [22,23,20]. As might be expected, it is predominantly expressed in the early stages of gestation during placental formation, and this high level of expression continues through the first trimester of pregnancy/ It is reduced by 50% during the second and third trimesters of gestation [22,24].…”
Section: General Information About S100p Proteinmentioning
confidence: 63%
“…Expression of the S100P protein is 90-to 200-fold higher in the placenta than in any other organ [22,23,20]. As might be expected, it is predominantly expressed in the early stages of gestation during placental formation, and this high level of expression continues through the first trimester of pregnancy/ It is reduced by 50% during the second and third trimesters of gestation [22,24]. S100P has been clearly demonstrated to be an important regulator of trophoblast invasion during placentation [22,[24][25][26].…”
Section: General Information About S100p Proteinmentioning
confidence: 94%
See 1 more Smart Citation
“…In a study by Tabrizi M. E. A. et al and Yue X. et al, it was found that S100P and FGF13 may act as regulators of trophoblastic invasion during the placentation period 33,34 . Incomplete invasion of trophoblasts results, for example, in a decrease of uteroplacental blood flow, a condition usually associated with preeclampsia 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 13 novel upregulated genes (10-13 fold) including Esm1, Slfn4, Usp18 and Grem1 and 4 downregulated genes (4-7 fold), including S100g, Pcp4, Col6a4, and Trpc3 were identified in the pregnant UA. While many of these genes were associated with gestational pathologies [34][35][36][37][38][39], the differential expression of these genes in healthy pregnancy relative to non-pregnancy suggests that these genes may have a unique role in gestational uterine vascular adaptations.…”
Section: Discussionmentioning
confidence: 99%